2011
DOI: 10.1001/archdermatol.2011.309
|View full text |Cite
|
Sign up to set email alerts
|

Patient Preferences for Psoriasis Treatments

Abstract: To assess patients' preferences for psoriasis treatments and to identify the effect of sociodemographic and socioeconomic characteristics on these preferences.Design: A computer-based conjoint analysis experiment was conducted to analyze the preferences of individuals with moderate or severe psoriasis for outcome attributes (probability, magnitude, and duration of benefit, as well as probability, severity, and reversibility of adverse effects) and process attributes (treatment location, frequency, duration, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(40 citation statements)
references
References 45 publications
3
36
1
Order By: Relevance
“…Five publications examined patient preferences for treatment; four of them described the results of a conjoint analysis based on a discrete choice experiment that aimed to analyze the preferences of individuals with moderate or severe psoriasis for outcome and process attributes4245 (Table 3). In a study published by Schaarschmidt et al,42 the attribute regarded as most important was treatment location (where the treatment takes place) (relative importance score [RIS]: 26.76), followed by probability of benefit (RIS: 23.77) and method of delivery (RIS: 23.49).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five publications examined patient preferences for treatment; four of them described the results of a conjoint analysis based on a discrete choice experiment that aimed to analyze the preferences of individuals with moderate or severe psoriasis for outcome and process attributes4245 (Table 3). In a study published by Schaarschmidt et al,42 the attribute regarded as most important was treatment location (where the treatment takes place) (relative importance score [RIS]: 26.76), followed by probability of benefit (RIS: 23.77) and method of delivery (RIS: 23.49).…”
Section: Resultsmentioning
confidence: 99%
“…In a study published by Schaarschmidt et al,42 the attribute regarded as most important was treatment location (where the treatment takes place) (relative importance score [RIS]: 26.76), followed by probability of benefit (RIS: 23.77) and method of delivery (RIS: 23.49). The RISs for all process attributes were higher than for adverse effect (AE)-related attributes, indicating that participants were willing to trade an increased risk of AEs for increased probability and magnitude of therapeutic benefit.…”
Section: Resultsmentioning
confidence: 99%
“…These results were consistent with an earlier report by Seston et al27 who found that attributes such as adverse effects, time to improvement, and relapse time frames influence treatment choices of individuals with psoriasis. Although Seston et al found a preference for minimizing the risk of adverse events, Schaarschmidt et al, in a 2011 study,26 reported that patients were willing to trade an increased risk of adverse events for better therapeutic outcomes. Unlike our study, neither study considered the previous treatment history of patients and how this might impact decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Suboptimal management of psoriasis can cause considerable physical impairment and have a strong impact on the emotional and social well-being as well as the socioeconomic status of patients [4,5,6]. Previous research showed that nonadherence to drugs may be an important reason for unsatisfactory efficacy of the treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research showed that nonadherence to drugs may be an important reason for unsatisfactory efficacy of the treatment. Many patients, especially those with severe psoriasis, are dissatisfied with the management of their disease and frustrated by the perceived ineffectiveness of the treatments, resulting in a high level of dissatisfaction and low adherence to treatments [4]. The rate of nonadherence may be as high as 40% of individuals with psoriasis [7].…”
Section: Introductionmentioning
confidence: 99%